2017
DOI: 10.1186/s12888-017-1294-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and related factors of depressive symptoms in hemodialysis patients in northern China

Abstract: BackgroundTo determine the prevalence of depressive symptoms and to explore related factors of depressive symptoms in hemodialysis (HD) patients in northern China.MethodsWe used a cross-sectional research design to recruit 227 chronic kidney disease (CKD) patients who were undergoing HD treatment in northern China during December, 2012 to March, 2013. The Chinese edition of the Center for Epidemiologic Studies Depression (CES-D) was used to measure depressive symptoms. Information on quality of life (QOL), act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
3
21
1
11
Order By: Relevance
“…DOPPS Phases 1–3 found that HD patients with poor social support were more likely to experience serum albumin <3.5 g/dL (OR = 1.18, 95% CI: 1.02–1.37) [ 201 ]. In contrast, HD patients with social support achieved better social interactions and coping mechanisms toward kidney disease [ 202 ], as well as fewer depression symptoms [ 208 ]. Ultimately, presence of social support enables patient self-efficacy to reach better health status.…”
Section: Non-iatrogenic Causes Of Malnutritionmentioning
confidence: 99%
“…DOPPS Phases 1–3 found that HD patients with poor social support were more likely to experience serum albumin <3.5 g/dL (OR = 1.18, 95% CI: 1.02–1.37) [ 201 ]. In contrast, HD patients with social support achieved better social interactions and coping mechanisms toward kidney disease [ 202 ], as well as fewer depression symptoms [ 208 ]. Ultimately, presence of social support enables patient self-efficacy to reach better health status.…”
Section: Non-iatrogenic Causes Of Malnutritionmentioning
confidence: 99%
“…A study found that mood was a deterrent factor in the level of acceptance of patients undergoing dialysis. 29 A study on the relationship between the spirituality le vel and acceptance of illness has shown positive results. This finding is consistent with a review of 110 studies prior to 2000 and 344 studies between 2000 and 2010 on the relationship of spirituality with mental and physical health, which shows that spirituality helps patients to adapt to a wide range of diseases or various conditions related to depression, general illness, chronic disease, kidney disease, diabetes, lung disease, cancer, blood disorders, heart and vascular disease, dental disease, eye problems, neurological diseases, HIV/AIDS, systemic lupus erythematosus, irritable bowel syndrome, musculoskeletal disease, caregiver burden, psychiatric illness, overall stress, natural disasters, and war or acts of terrorism.…”
Section: Discussionmentioning
confidence: 99%
“…A multinational cross-sectional study found that the prevalence of depression was up to 46% from 2278 HD participants [6]. The depression symptoms of HD patients are associated with a series of adverse outcomes, for instance, lower treatment compliance [7,8], malnutrition, increased morbidity [9], decreased quality of life, higher rates of hospitalisation and mortality among HD patients [10][11][12]. However, depression issues are often under recognized and untreated [13].…”
Section: Introductionmentioning
confidence: 99%